My iMovie - Grothaus, Michael (Que, 2014)
Step-by-step instructions with callouts to iMovie screenshots that show you exactly what to do. Help when you run into iMovie problems or limitations. Tips and Notes to help you get the most from iMovie. Full-color, step-by-step tasks walk you through everything you want to do with iMovie. Learn how to: • Become familiar with the layout of the new iMovie for Mac interface • Organize and manage your iMovie Library, videos, photos, and other digital media • Import your videos into iMovie • Precisely trim movie clips to show exactly what you want in your movie • Correct shaky or blurry video • Enhance your audio and create a voiceover • Add background music and sound effects • Use themes to make your movies look polished • Add titles and special effects to your movie • Create a high-quality trailer to give your friends a sneak peek at what is to come • Share your movies on social media like Facebook, or via email • Bonus Chapter: Using iMovie on your iPhone, iPad, and iPod touch • Add transitions between clips to move smoothly from one clip to the next • Overlay one clip or photo on top of another to combine them into one image.